A profile about the Kibutz - Ospino Edery, Ysaac (2014)
The kibbutz is an original and unique creation Israeli, a society of multiple generations, rural, characterized by their lifestyle community, collective and cooperative, of democratic management, with responsibility for the welfare of each independent member of sex, age, and ownership of their means of production and consumption.Today Kibbutz, its main income obtained them by different industrial activities of Vanguard, which are located in the periphery of the country. This profile includes a historical assessment of the emergence and evolution of the kibbutz, its main activities, industrial and agricultural, as well to as they are organized to deal with the global market, also a condensed review of trade relations Peru and Israel.